'Akhlaqiyyaat Ta’allum Al-Lughat Al-‘Arabiyyaat Fii Al-Qarn Al-Haadii Wa ‘Ishriin - Uqba, M Sholih Salimul; Nasution, Rodiah; Muhammad Fadli Ramadhan (Al Intisyar: Jurnal Pendidikan Bahasa Arab, 2024)
The 21st century makes learning Arabic with existing technology requires attention to learning ethics. The ethics of learning Arabic in the 21st century with technology involves manners towards the Arabic language, technology, teachers and fellow learners. A learner needs to respect Arabic as a noble and holy language, use technology wisely and responsibly, and respect the role of the teacher as the main source of learning. In addition, learners also need to maintain manners towards fellow learners by respecting, helping, and maintaining each other's feelings in the process of learning Arabic. The application of Arabic learning ethics in the 21st century with technology can be done through several concrete steps. First, learners need to study Arabic seriously, use Arabic properly and correctly, and avoid using Arabic for inappropriate things. Second, learners need to follow the instructions for using Arabic language learning applications properly and avoid misusing applications for plagiarism or spreading false information. Third, learners should remain active in communicating with teachers, ask questions when experiencing difficulties, and respect the explanations and guidance given. Fourth, in interactions with fellow students, respect each other, avoid insults, and maintain an attitude of mutual help and support in understanding learning materials.